DEFENSE MECHANISM OF THE MAIN CHARACTER IN LAURIE HALSE ANDERSON’S SPEAK NOVEL - Ritsnaini Zulfaisya; Hasnini Hasra (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT This study is a defense mechanism analysis of the main character in Laurie Halse Anderson’s Speak novel. It aims at revealing how defense mechanisms is experienced by Melinda Sordino as the main character of Speak novel by applying Sigmund Freud’s defense mechanism theory. The data is the narration and dialogue in the narrative implying defense mechanism strategies used by the main character in coping up with verbal, physical and phsychological bullying she experienced. This study uses a descriptive qualitative method. The finding shows that the main character had repression, rationalization, regression, reaction-formation, projection, replacement, isolation, identification, sublimation and turning to self as defense mechanisms strategies to oversome the conflicts. Keywords: main character; defense mechanisms; phsychoanalysis.